Innovation, inclusion and integration : from transition to convergence in Eastern Europe and the former Soviet Union - Mitra, Pradeep (World Bank, 2008)
It will be of particular interest to policy makers, government officials, researchers, and economists interested in fostering inclusive economic growth in the countries of the region and their deeper integration into the global economy."--BOOK JACKET.